A Systematic Review of TPACK Implementation in Indonesian Language Education in the Digital Era. - Tiffani Iftina Al-Huwaida; Fathan Riski Efendi (Vol. 3 No. 1 (2025): Proceeding of International Conference on Cultures & Languages 2025, 2025)
The transformation of education in the digital era requires educators to possess competencies that effectively integrate technology, pedagogy, and learning content. This study aims to formulate practical recommendations for educators and curriculum developers to optimally integrate TPACK into Indonesian language learning by identifying its impact on language skills. The research method employed is a Systematic Literature Review (SLR) of national and international scholarly publications published between 2020 and 2025. Literature searches were conducted through databases such as Google Scholar, and SINTA. Inclusion criteria covered studies discussing the implementation of TPACK in early childhood education, primary schools, and secondary schools within the context of teaching Indonesian language. Based on a total of 12 scholarly publications, the findings reveal that 25% reported the application of TPACK positively impacted receptive language skills (listening and reading), 42% influenced expressive language skills (writing and speaking), and 33% affected non-language skills (learning autonomy, learning motivation, and improved learning outcomes). Overall, the implementation of TPACK aligns with the demands of education in the digital era by helping educators integrate subject content with technology, particularly in language skills. However, there is still a scarcity of scholarly publications examining the effectiveness of this method in Indonesian language instruction. Therefore, in addition to recommending the application of this teaching model, this study is also expected to serve as a reference for future research.